T cell receptor-zeta and granzyme B expression in mononuclear cell infiltrates in normal colon mucosa and colon carcinoma. Issue 1 (January 1997) - Mulder, W M; Bloemena, E; Stukart, M J; Kummer, J A; Wagstaff, J; Scheper, R J
Abstract : BACKGROUND: Whereas the presence of a lymphoid infiltrate has been associated with a favourable prognosis in colorectal carcinoma, the proliferative and cytotoxic responses of freshly isolated tumour infiltrating lymphocytes are frequently impaired. In mice, tumour induced immune suppression has been associated with a decreased expression of the zeta-chain of the T cell receptor (TCR)-CD3 complex, and loss of mRNA for granzyme B. AIM: To compare the expression of TCR-zeta and granzyme B in lymphocytes infiltrating normal colonic mucosa and Duke's A and D colorectal carcinomas. SPECIMENS: Paraffin wax embedded normal (n = 10) and malignant colonic mucosa (seven Dukes's A, nine Dukes's D). METHOD: Immunohistochemistry. RESULTS: The numbers of TCR-zeta + lymphocytes decreased from normal mucosa to Dukes's D carcinomas. In contrast, granzyme B+ lymphocytes were more frequent in Dukes's A carcinomas than in normal mucosa, but disappeared from advanced stage tumours. Granzyme B expressing cells were mainly CD3- (natural killer/lymphokine activated killer cells) in normal mucosa, but CD3+ in tumours, indicating the presence of activated cytotoxic T lymphocytes. In vitro culture of tumour infiltrating lymphocytes rapidly restored the expression of both molecules. CONCLUSION: The frequency of TCR-zeta + and granzyme B+ lymphocytes is decreased in advanced stage colorectal carcinomas. The restoration of expression during in vitro stimulation suggests the presence of tumour derived suppressive factors in situ.